(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Cancer is defined by the uncontrolled development of aberrant cells that may infiltrate and destroy surrounding tissues. This description suggests that all cancer cells inside a tumour are aberrant in the same way, and therefore have the same ability to start and maintain the tumour. It has long been recognized that the individual cells that make up a tumour may have considerable functional and morphologic heterogeneity. A growing body of data suggests that many solid tumour are structured in a hierarchical fashion, with the small fraction of cancer stems cells as well as tumors initiating cell driving tumour development. These cell are the only ones capable of starting and driving tumour development, although making up a tiny proportion of the total tumour population. CSCs may be resistant to chemotherapy as well as radiation treatment, according to new research, which has sparked a lot of discussion and curiosity about their potential therapeutic use.